2018
DOI: 10.1002/anie.201811060
|View full text |Cite
|
Sign up to set email alerts
|

Helical Nanostructures: Chirality Transfer and a Photodriven Transformation from Superhelix to Nanokebab

Abstract: Photosensitive cinnamic acid conjugated glutamides were designed to demonstrate photocontrolled hierarchical chirality transfer and switching in self‐assembled systems. In methanol, the cinnamic acid derivatives self‐assembled into superhelices, which could be switched into nanokebabs upon UV irradiation. These two nanostructures showed opposite helicity. The chiral nanostructures could further convey their chirality to achiral fluorescent molecules and result in the emission of circularly polarized luminescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 161 publications
(103 citation statements)
references
References 76 publications
1
101
0
1
Order By: Relevance
“…As shown in Figure 22B, a photosensitive cinnamic acid derivative (lor d-CG), which could be dimerized along with a large change in molecular packing, can successfully switch the nanostructure from a superhelix to a nanokebab, as well as having supramolecular chirality. [198] Moreover, these helical nanostructures can serve as matrixes to convey their helicity to fluorescent achiral dyes (CBS) and emit CPL. Upon irradiating with UV light (365 nm), these superhelices turned into nanokebabs, and both the helicity and CPL were inverted.…”
Section: Cpl Switchesmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 22B, a photosensitive cinnamic acid derivative (lor d-CG), which could be dimerized along with a large change in molecular packing, can successfully switch the nanostructure from a superhelix to a nanokebab, as well as having supramolecular chirality. [198] Moreover, these helical nanostructures can serve as matrixes to convey their helicity to fluorescent achiral dyes (CBS) and emit CPL. Upon irradiating with UV light (365 nm), these superhelices turned into nanokebabs, and both the helicity and CPL were inverted.…”
Section: Cpl Switchesmentioning
confidence: 99%
“…B) Reproduced with permission. [198] Copyright 2018, Wiley-VCH. C) Molecular structure of the axially chiral binaphthyl-2,2′-bipyridyl cyclic dyad at protonated and deprotonated states.…”
Section: Cpl Switchesmentioning
confidence: 99%
“…[22,23] Amongst the anisotropic architectures, helical architectures have attracteds peciala ttention in view of their chiroptical properties, and the unique arrangemento fc hemicalf unctionalitiesi ns pace offered by them. [24,25] The chirality inherent in the molecularb uilding block can be translated into the supramolecular chirality of the self-assembly.R ecently,D ing and Miyakou tilized lipid nanotubes (LNT) obtained from ac o-assembly of ag lucopyranosylamide and oleic acidt op repare coiled PDA-LNT hybrids with strongp hoto-thermal conversion ability. [26] Nonetheless, chirality control on the coilingw as not demonstratedb yt hem.…”
mentioning
confidence: 99%
“…At present, [2 + 2] photodimerizations are among the most extensively studied organic solid-state reactions [16], but there are a few reports on the effect of [2 + 2] photocycloaddition reaction on supramolecular gels. For example, Liu et al [17] reported photo-sensitive cinnamic acid conjugated glutamides (L/D-CG), which could self-assemble into superhelix in methanol and then switched into nanokebab upon UV irradiation. In the gelled state, the molecules are close enough to each other due to noncovalent bonding/π-π stacking, making it much easier for dimerization to occur than in solution.…”
Section: Introductionmentioning
confidence: 99%